MRI measurement of wall shear stress vectors in bifurcation models and comparison with CFD predictions. - Köhler,U; Marshall,I; Robertson,MB; Long,Q; Xu,XY; Hoskins,PR (J Magn Reson Imaging, 2001)
Steady fluid flow was studied in a simple bifurcation model and in a physiologically realistic model of the human carotid bifurcation. Wall shear stress (WSS) vectors were calculated from phase-contrast (PC) magnetic resonance imaging (MRI) measurements of the velocity field. Velocity measurements in the inflow regions were also used as boundary conditions for computational fluid dynamics (CFD) calculations of WSS, which were compared with those derived from MRI alone. In regions of well-behaved flow, MRI and CFD estimates of WSS were in good general agreement. In regions of disturbed flow, for example near the bifurcation, the quality of the MRI measurements was sufficient for reliable calculation of WSS vectors when a sensitive surface coil was used. The combination of MRI and CFD would seem to be a powerful technique for the investigation of flow phenomena.